American Law - Kermit L. Hall (Oxford University Press, 2002)
The Oxford Guide to American Law gives readers a comprehensive, authoritative, & accessible guide in the form of 408 alphabetically arranged entries witten by hundreds of respected scholars about a wide range of subjects, such as biographies, discussions of central concepts, overview of current controversies, definitions & descriptions, & summaries of important legal cases.